The Congenital Cardiology Cloud: Proof of feasibility of Germany's first tele-medical network for pediatric cardiology - Klais, Marko; Doll, Ulrike; Purbojo, Ariawan; Dittrich, Sven; Rottermann, Kathrin (Journal of Telemedicine and Telecare, 2023)
Background: For an optimal interplay based on the data-secure exchange of diagnostic data between patients, ambulatory care, and hospital care, we implemented the first tele-medical network for pediatric cardiology in Germany, the Congenital Cardiology Cloud. This study focuses on its feasibility, technical characteristics, and implementation in routine clinical work. Methods: Tele-medical traffic comprised numbers of incoming/outgoing data, related file types, treatment options for tele-medically processed patients, and patient classification with respect to the severity of disease. Proof of feasibility was related to the number of successful tele-medical transmissions of discharge documents at the end of the observation period (02/2020–10/2020). Results: Analysis of Congenital Cardiology Cloud's data communication showed a number of 1178 files for a total of 349 patients, favoring transmissions towards the clinic. Incoming traffic was predominantly characterized by diagnostic data regarding tele-consultations (76.6%), consisting of a multitude of file types, whereas 93.4% of the dispatched data corresponded to discharge letters. The number of tele-consultations counted up to 61, with a necessary subsequent treatment or diagnostic procedure in 90.2% of the presented cases. Tele-medically processed patients generally showed to be more complex (severe chronic heart disease 42.4% vs. 23.7%). At the end of the observation period, 97.6% of the discharge documents were transmitted via telemedicine. Discussion: The implementation of the first tele-medical network for pediatric cardiology in Germany proves recent technological developments to successfully enable innovative patient care, connecting the ambulatory and hospital sector for a joint patient advice, predominantly in more complex cases. Possible governmentally guided refinancing concepts will show its long-term feasibility.
CRIS-Team Scopus Importer:2023-04-07
Keywords: cloud-based healthcare; congenital heart disease; pediatric cardiology; teleconsulting; Telemedicine